Supported MoOx and WOx solid acids for biomass valorization: interplay of coordination chemistry, acidity, and catalysis - Sudarsanam, Putla; Gupta, Navneet Kumar; Mallesham, Baithy; Singh, Nittan; Kalbande, Pavan Narayan; Reddy, Benjaram M.; Sels, Bert F. (ACS Catalysis, 2021)
Supported molybdenum oxide (MoOx) and tungsten oxide (WOx) materials are a vital class of solid acid catalysts for the chemical industry because of their nontoxic nature, strong acidity, remarkable stability in water, hydrogen, and oxygen atmospheres, and excellent reusability performance. These fascinating solid acids play a pivotal role in developing sustainable catalytic routes for renewable biomass processing to produce value-added fuels, chemicals, and platform molecules. The coordination chemistry of MoOx and WOx on the support materials (oxides, carbons, or zeolites) controls their acidic strength, active site accessibility, and catalytic activity. Hence, significant efforts have been made toward optimizing the conditions used for catalyst synthesis and biomass processing to tune the coordination chemistry of MoOx and WOx with the substrate molecules and, thus, their acid-activity/selectivity performance. This Review provides a comprehensive overview of supported MoOx and WOx solid acids for biomass valorization. The importance of the biomass and the role of solid acids for biomass valorization were emphasized, followed by a brief discussion of supported MoOx and WO(x )solid acids. Afterward, the interplay of coordination chemistry, acidic strength, and catalytic activity of supported MoOx and WOx solid acids was discussed. Finally, their catalytic applications for the valorization of several biomass substrates and their derivatives were summarized. This Review will provide valuable insights for developing advanced supported WOx and MoOx solid acids for catalytic biomass valorization and other challenging acid-catalyzed processes.
Keywords: Acidity; biomass valorization; catalysis; Coordination chemistry; molybdenum oxide; tungsten oxide

Efficient cascade C-N coupling reactions catalyzed by a recyclable MoOx/ Nb2O5 nanomaterial for valuable N-heterocycles synthesis - Singh, Nittan; Kalbande, Pavan Narayan; Umbarkar, Shubhangi; Sudarsanam, Putla (Molecular Catalysis, 2022)
The efficient cascade synthesis of pharmaceutically valuable N-heterocycles at solvent-free conditions was achieved using a robust, recyclable MoOx/Nb2O5 nanocatalyst. The results of catalyst screening revealed that the MoOx/Nb2O5 nanorods, calcined at 500 degrees C (MoNb5), exhibit excellent catalytic activity in the oxidative coupling of benzylamine with 96.5% conversion and >99.6% selectivity to the desirable imine product. The uniform dispersion of Mo-oxide nanoparticles (average particle size: 5.2 +/- 0.5 nm) on shape-controlled Nb2O5 nanorods (width: 5.3 +/- 0.5 nm and length: 23-38 nm) in MoNb5 catalyst led to improved structural and acid properties, beneficial for the cascade C-N bond construction. The shape-controlled MoNb5 catalyst showed versatile activity in various cascade C-N coupling reactions to obtain 2-phenylbenzimidazole, 2-phenyl-quinaxoline, and 2-phenyl-2,3-dihydroquinazolin-4(1H)-one with good to excellent yields at solvent-free con-ditions. The optimum ratio of Lewis/Bronsted acid sites, the unique structure of Nb2O5 nanorods, and the strong MoO3-Nb2O5 interaction are the key reasons for the higher activity of MoNb5 catalyst. The efficient reusability of MoNb5 catalyst, its remarkable activity in diverse N-heterocycles synthesis, and efficient gram-scale synthesis emphasize its practical application for the cascade C-N coupling reactions under benign conditions.
Keywords: Acid sites optimization; Cascade C-N bond formation; Diverse nitrogenous chemicals; Heterogeneous nanosized catalyst; MoO3-Nb2O5 interaction; Nb2O5 nanorods

Shape-controlled nanostructured MoO3/CeO2 catalysts for selective cyclohexene epoxidation - Sudarsanam, Putla; Singh, Nittan; Kalbande, Pavan Narayan (Catalysis Communications, 2022)
This study reported a vital role of CeO2 shape on the structure-activity properties of MoOx/CeO2 catalysts for cyclohexene epoxidation. Uniform dispersion of MoOx on the surface of shape-controlled CeO2 nanocubes (average particle size: 23.5 nm) and nanorods (average width: 6.3 nm and length: 15-95 nm) was found in MoOx/CeO2 nanomaterials. The MoOx/CeO2 nanocubes showed higher epoxide selectivity (97.3%) with 98.9% cyclohexene conversion, although it has lower BET surface area (30.2 m(2)/g) compared with MoOx/CeO2 nanorods (72.8 m(2)/g). The presence of more electropositive Mo6+ species and the strong Mo-Ce interaction led to improved catalytic efficacy of MoOx/CeO2 nanocubes in cyclohexene epoxidation.
Keywords: CeO2 nanocubes; CeO2 shapes; Nanosized MoOx/CeO2 catalyst; Selective epoxidation; Structure-activity properties

One-pot synthesized efficient molybdenum-niobium-oxide nanocatalyst for selective C-O and C-N coupling reactions at mild conditions - Kalbande, Pavan Narayan; Singh, Nittan; Swapna, Bhattu; Umbarkar, Shubhangi; Sudarsanam, Putla (Catalysis Communications, 2023)
An efficient molybdenum-niobium-oxide nanomaterial was synthesized by a one-pot hydrothermal method for selective C-O (glycerol ketalization) and C-N coupling (benzylamine oxidation) reactions. The catalytically favourable properties, such as defective metal sites, truncated surfaces, and uniform metal dispersion in the MoO3-Nb2O5 nanorods, calcined at 500 degrees C (MoNb OPS-5), were confirmed by Raman, HR-TEM, and STEM-EDX, respectively. Because of improved Lewis/Bronsted acidic strength, the MoNb OPS-5 catalyst showed higher activity in glycerol ketalization and benzylamine oxidation at mild conditions, giving superior selectivity to solketal (97%) and dibenzylimine (99%), respectively. The MoNb OPS-5 catalyst showed high structural stability and considerable good reusability efficacy.
Keywords: C-O and C-N coupling; Glycerol and benzylamine; Mo-Nb-O nanocatalyst; nanocatalysts; One-pot hydrothermal synthesis

Photocatalytic C-N bond construction toward high-value nitrogenous chemicals - Li, Jie; Liu, Tengyu; Singh, Nittan; Huang, Zhuochun; Ding, Yan; Huang, Jinshu; Sudarsanam, Putla; Li, Hu (Chemical Communications, 2023)
The construction of carbon-nitrogen bonds is vital for producing versatile nitrogenous compounds for the chemical and pharmaceutical industries. Among developed synthetic approaches to nitrogenous chemicals, photocatalysis is particularly prominent and has become one of the emerging fields due to its unique advantages of eco-sustainable characteristics, efficient process integration, no need for high-pressure H2, and tunable synthesis methods for developing advanced photocatalytic materials. Here, the review focuses on potential photocatalytic protocols developed for the construction of robust carbon-nitrogen bonds in discrepant activation environments to produce high-value nitrogenous chemicals. The photocatalytic C-N bond construction strategies and involved reaction mechanisms are elucidated. This review focuses on potential photocatalytic protocols developed for the construction of robust carbon-nitrogen bonds in discrepant activation environments to produce high-value nitrogenous chemicals.

Shape-controlled MoO3/MnO x nanocatalyst for the selective synthesis of 2-phenylquinoxaline drug motifs - Singh, Nittan; Putla, Suresh Babu; Pratap Singh, Chandrodai; Kalbande, Pavan Narayan; Choudhary, Priyanka; Krishnamurty, Sailaja; Krishnan, Venkata; Bhatte, Kushal; Sudarsanam, Putla (ACS Applied Nano Materials, 2023)
We have developed a highly effective shape-controlled MoO3/MnOx nanocatalyst for the selective synthesis of 2-phenylquinoxaline drug motifs at room temperature without any external oxidant. Electron microscopy images reveal that the MnOx material contains rod-shaped particles (length: 500-1000 nm and width: 150-200 nm) and the MoO3 species are uniformly dispersed in the MoO3/MnOx material. The MoO3/MnOx nanocatalyst calcined at 500 degrees C (MoO3/MnOx-5) contains abundant strong acid sites and an optimum ratio of Mn4+/Mn3+, which are responsible for the C-N cross-coupling reaction between 2-phenylethylamine and o-phenylenediamine, giving higher yields (>96%) of 2-phenylquinoxaline at mild conditions. The broad scope of this catalytic strategy at room temperature and without an external oxidant was confirmed by achieving >90% yields of functional 2-phenylquinoxalines from C-N cross-coupling of various o-phenylenediamines and 2-phenylethylamines. The outstanding reusability efficiency of the MoO3/MnOx-5 nanocatalyst up to five cycles without the need for a regeneration step as well as the effective scalability highlighted the practicability of the MoO3/MnOx-based catalytic protocol for carbon-heteroatom coupling reactions at room temperature and without an external oxidant. Using computational studies, the possible reasons for the selective synthesis of 2-phenylquinoxaline over the MoO3/MnOx-5 nanocatalyst were elucidated.
Keywords: cascade C-N cross-coupling; DFT studies; room temperature andopen air; shape-controlled MoO3/MnOx nanocatalyst; structure-activity correlation

Durable and stable bifunctional Co3O4-based nanocatalyst for oxygen reduction/evolution reactions - Chutia, Bhugendra; Chetry, Rashmi; Rao, Komateedi N.; Singh, Nittan; Sudarsanam, Putla; Bharali, Pankaj (ACS Applied Nano Materials, 2024)
The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are recognized as the core reaction processes in regenerative energy storage and conversion systems. The design of cost-effective and high-performance bifunctional ORR/OER electrocatalysts (ECs) is very important for their substantial commercialization. Herein, sponge-like Co3O4 nanoparticles anchored on carbon (Sp-Co3O4/C) are successfully fabricated by a facile two-step solvothermal strategy for ORR/OER in an alkaline electrolyte. The Sp-Co3O4/C EC exhibits promising bifunctional ORR/OER activity with ORR onset potential (E onset = 0.88 V vs RHE), half-wave potential (E (1/2) = 0.75 V), limiting current density (j = -6.60 mA cm(-2)), OER onset potential (E-onset = 1.26 V), and OER overpotential for 10% energy conversion (eta(10) = 0.38 V) in 0.1 M KOH. It demonstrates a significantly lower reversibility index (Delta E = E- j10 - E 1/2 = 0.86 V), comparable to standard Pt/C and RuO2 ECs. The superior ORR/OER performances of Sp-Co3O4/C EC can be ascribed to the synergistic contribution of a high electrochemically active surface area (48.33 m(2) g(-1)), BET surface area (131 m(2) g(-1)), the rich interfacial structure of the crystal facets (111), (220), and (311), and the abundant oxygen vacancies in the sponge-like morphology. Besides the methanol tolerance, accelerated durability and chronoamperometric test established excellent durability and stability in the electrocatalytic operation. This work offers insight into the development of high-performance ORR/OER ECs. [GRAPHICS]
Keywords: bifunctional; fuel cell; interface; oxygen evolution; oxygen reduction; Oxygen vacancy; Sp-Co3O4/C; sponge-like morphology

Efficient glycolysis of used PET bottles into a high-quality valuable monomer using a shape-engineered MnO nanocatalyst - Swapna, Bhattu; Singh, Nittan; Patowary, Suranjana; Bharali, Pankaj; Madras, Giridhar; Sudarsanam, Putla (CATALYSIS SCIENCE & TECHNOLOGY, 2024)
Keywords: Catalyst; kinetics; Nanorods; Oxidation; Oxides; POLY(ETHYLENE-TEREPHTHALATE); WASTE

Valorizing biomass waste glycerol to fuel additive at room temperature using a nanostructured WO3/Nb2O5 catalyst - Putla, Suresh Babu; Subha, P.; Swapna, Bhattu; Singh, Nittan; Sudarsanam, Putla (Catalysis Communications, 2024)
We developed a nanostructured catalyst consisting of WO3 nanoparticles and Nb2O5 nanorods for efficient glycerol acetalization to produce a fuel additive (solketal) at room temperature. Particularly, the WO3/Nb2O5 nanocatalyst calcined at 400 degrees C (WO3/Nb2O5-4) contains W5+ species and optimum acid sites, which enhanced glycerol conversion (92.3%) with 95.6% of solketal selectivity at room temperature. The structure stability of the WO3/Nb2O5-4 catalyst during the reaction is showcased by hot-filtration study and XRD/XPS characterization. However, the inadequate regeneration of the Bronsted acid sites led to a gradual decrease in the recyclable activity of the WO3/Nb2O5-4 catalyst.
Keywords: Bronsted-Lewis acid sites; Fuel additive; Room-temperature glycerol acetalization; W5+species

Additive-free, selective synthesis of N-heteroaromatics using morphology-engineered hollow CeO2 nanocatalyst - Singh, Nittan; Swapna, Bhattu; Balu, Alina Mariana; Bhatte, Kushal; Sudarsanam, Putla (ACS Sustainable Chemistry & Engineering, 2025)
We developed a highly efficient, shape-controlled CeO2 nanocatalyst for synthesizing N-heteroaromatics via an aerobic dehydrogenation approach, operating at mild reaction conditions without needing toxic acid/base additives. Different morphologies of CeO2, namely, hollow nanospheres, nanorods, and irregularly shaped nanoparticles, were synthesized, as confirmed by electron microscopy analysis. The CeO2 hollow nanosphere catalyst (CeO2-HNS) exhibited unique features, such as abundant acid-base sites, larger-sized voids, and surface oxygen vacancies. These characteristics are found to be crucial for the additive-free oxidative dehydrogenation of saturated N-heterocycles over the CeO2-HNS catalyst, resulting in 98% conversion of 1,2,3,4-tetrahydroquinoline with 100% quinoline product selectivity. The versatility of this approach was further demonstrated by the successful aerobic dehydrogenation of a broad range of saturated N-heterocycles, affording N-heteroaromatics in good to excellent yields. Furthermore, the CeO2-HNS nanocatalyst showed exceptional reusability over six cycles without requiring a regeneration step, such as high-temperature calcination treatment. The structural and morphological stability of the CeO2-HNS catalyst, along with reaction scalability and favorable green chemistry metrics, emphasized the practical viability of the CeO2-HNS catalyst for industrial applications.
Keywords: acid-base and defect sites; additive-free aerobicdehydrogenation; CeO2 hollow nanosphere catalyst; N-heteroaromatics; reusability and scalability